1982
DOI: 10.1051/rnd:19820105
|View full text |Cite
|
Sign up to set email alerts
|

Relation entre l'espace de diffusion de l'eau lourde mesurée in vivo et le volume hydrique corporel des bovins en croissance

Abstract: Summary. Relation in vivo between the dilution space of deuteriated water and body water in growing cattle.Twenty-one Charolais and 21 Friesian bulls were infused with deuteriated water (0.6 g/kg body weight). Blood samples were collected 6,9 and 24 hours after infusion. The dilution space was calculated by either the zero-time extrapolation method (EDC o ) or by 6-hour marker concentration in blood water (EDC 6 100 of ECV). The EDC 6 overestimated by 4.7 p. 100 the ECTC and was less related to it (SE of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Nagy and Costa (1980) discussed some sources of errors in using isotopes to measure water fluxes in animals that are pertinent to measuring total body water. In the 30 steers used in the present experiment, overestimation of total body water was 6.9%, whereas 3.2% overestimation was observed by Robelin (1982) and 7.6% by Pfau and Salem (1972). The degree of overestimation was higher when a single blood sample was used to calculate total body water (12%, Bird et al, 1982;15%, Carnegie and Tulloh, 1968;16%, Meisner et al, 1980;20%, Little and McLean, 1981).…”
Section: Discussionmentioning
confidence: 45%
“…Nagy and Costa (1980) discussed some sources of errors in using isotopes to measure water fluxes in animals that are pertinent to measuring total body water. In the 30 steers used in the present experiment, overestimation of total body water was 6.9%, whereas 3.2% overestimation was observed by Robelin (1982) and 7.6% by Pfau and Salem (1972). The degree of overestimation was higher when a single blood sample was used to calculate total body water (12%, Bird et al, 1982;15%, Carnegie and Tulloh, 1968;16%, Meisner et al, 1980;20%, Little and McLean, 1981).…”
Section: Discussionmentioning
confidence: 45%
“…Preliminary studies on a few animals (Doreau, Martin-Rosset and Dubroeucq, 1982) have shown a weak relationship between milk intake and foal growth. This relationship is stronger in other species such as cattle (Le Neindre, 1974) Doreau and Dussap (1980) (Robelin, 1982) (Meyer and Ahlswede, 1976) and at 4 months (Schryver et al, 1974), taking into consideration the differences in maturity between heavy and light breeds for a same body weight. It was assumed that the body water/fat-free mass ratio was the same for the two types at the same maturity, Protein weight was estimated as 79 % of fat-free dry matter from bibliographical data on 4-month old foals.…”
mentioning
confidence: 99%
“…Water in gut contents and empty body water were estimated by using the 1CMR (Loy, 1983), with the exception that a 6% overestimation of total body water was assumed instead of 3.2%. A 6% overestimation was the average amount of overestimation in experiments reported by Pfau and Salem (1972), Robelin (1982) and Arnold et al (1985). A two-compartment model (2CM) and a threecompartment model (3CM), based upon the kinetics of the models (Shipley and Clark, 1972) were solved for compartment volumes.…”
Section: Methodsmentioning
confidence: 99%